Sensus Fidei Umat Katolik di Keuskupan Agung Jakarta terhadap Isu Homoseksualitas pada Tahun 2022: Sensus Fidei of the Parishioners of the Archdiocese of Jakarta on the Subject of Homosexuality in 2022 - Adiwenanto, Albertus (DISKURSUS - JURNAL FILSAFAT DAN TEOLOGI STF DRIYARKARA, 2023)
Homosexuality is not easily accepted in the Catholic Church. There are at least three major schools concerning the attitude towards homosexuality based on their respective theological methodologies (scientia fidei). The first school is encapsulated in the Letter to the Bishops of the Catholic Church on the Pastoral Care of Homosexual Persons (1986), which rejects homosexual persons and same-sex sexual relationships. The second school is put forward by John J. McNeill (1993), a moralist who embraces homosexual persons and same-sex sexual relationships. The last one is represented by the document of Amoris Laetitia (2016), which accepts homosexual persons but disapproves of same-sex sexual relationships. These three major schools refer to the interpretation of the document Persona Humana article 8 (1975). A survey of 566 respondents was conducted from the 8th to the 15th of November in 2022. The results show that 74.2% of respondents have a form of acceptance in accordance with Amoris Laetitia, 14.5% with the Letter to the Bishops of the Catholic Church on the Pastoral Care of Homosexual Persons, and 5.5% with the thoughts of John J. McNeill. Our study concluded that accepting homosexual persons and rejecting homosexual acts is the reference for ad experimentum moral decisions in the context of the Archdiocese of Jakarta in 2022. Abstrak Homoseksualitas tidak begitu mudah diterima dalam Gereja Katolik. Setidaknya ada tiga aliran yang berbeda sikap terhadap homoseksualitas berdasarkan pandangan teologi (scientia fidei) masing-masing. Aliran pertama terwakili oleh dokumen Letter to the Bishops of the Catholic Church on the Pastoral Care of Homosexual Persons (1986) yang menolak pribadi homoseksual dan hubungan seksual sesama jenis. Aliran kedua diwakili oleh seorang moralis bernama John J. McNeill (1993) yang menerima pribadi homoseksual dan hubungan seksual sesama jenis. Aliran ketiga terwakili oleh dokumen Amoris Laetitia (2016) yang menerima pribadi homoseksual namun menolak hubungan seksual sesama jenis. Ketiga aliran besar ini mengacu pada penafsiran dokumen Persona Humana artikel 8 (1975). Sejak tanggal 8 sampai dengan 15 November 2022 kami melakukan survei terhadap 566 responden. Hasil survei menunjukkan sebanyak 74.2% responden memiliki bentuk penerimaan sesuai dengan Amoris Laetitia; sebanyak 14.5% responden memiliki bentuk penerimaan sesuai dengan dokumen Letter to the Bishops of the Catholic Church on the Pastoral Care of Homosexual Persons; dan sebanyak 5.5% responden memiliki bentuk penerimaan sesuai dengan pemikiran John J. McNeill. Kami menyimpulkan bahwa sikap menerima pribadi homoseksual dan menolak tindakan homoseksual merupakan rujukan keputusan moral ad experimentum dalam konteks Keuskupan Agung Jakarta di tahun 2022. Kata-kata Kunci: Homoseksualitas, Persona Humana, Amoris Laetitia, John J. McNeill, sensus fidei, scientia fidei